A platform of regioselective methodologies to access polysubstituted 2-methyl-1,4-naphthoquinone derivatives: scope and limitations - Cesar-Rodo, Elena; Feng, Liwen; Jida, Mouhamad; Ehrhardt, Katharina; Bielitza, Max; Boilevin, Jérémy; Lanzer, Michael; Williams, David Lee; Lanfranchi, Don Antoine; Davioud-Charvet, Elisabeth (European journal of organic chemistry, 2016)
A platform of synthetic methodologies has been established to access a focused library of polysubstituted 3-benzylmenadione derivatives functionalized on the aromatic ring of the naphthoquinone core. Two main routes were explored: 1) The naphthol route, starting from either an α-tetralone or a propiophenone, and 2) the regioselective Diels?Alder reaction, starting from various dienes and two 2-bromo-5(or 6)-methyl-1,4-benzoquinones. 6-Substituted 2-methylnaphthols were synthesized by using a xanthate-mediated free-radical addition/cyclization sequence for the construction of the 6-substituted menadione subunit. Furthermore, an efficient and simple new pathway that allows the formation of 6- or 7-substituted 3-(substituted-benzyl)menadione regioisomers from a common commercial scaffold has also been developed by the naphthol route, advantageous with regard to step economy. Our synthetic methodologies exemplified by 34 compounds have allowed structure?activity relationships to be deduced for use as the basis for the development of new antimalarial redox-active polysubstituted benzylmenadione derivatives.
Gesehen am 30.04.2020